Melt flow index of low-density polyethylene determination based on molecular weight and branching properties. (November 2019) - Azmi, A; Sata, S A; Rohman, F S; Aziz, N
Abstract: Industrially, a low-density polyethylene (LDPE) is characterized based on their Melt Flow Index (MFI). In numerous publication, LDPE's MFI is correlated to its average molecular weight (Mw). An overview of modeling studies on LDPE reactors available in the open literature indicates significant discrepancies among researchers for the correlation of MFI-Mw, therefore a research to produce reliable correlation need to be carried out. This research gathers various experimental and industrial data of different LDPE product grades. Empirical correlations between MFI and Mw are developed and the analysis on the MFI and Mw relation is addressed. The percentage of error between the model prediction and industrial data varies from 0.1% to 2.4% which can be considered minimum. The nonlinear model obtained indicates the competency of the developed equation to describe the variation of industrial data, thus allowing greater confidence in LDPE's MFI prediction.